Mechanism of 53BP1 activity regulation by RNA-binding TIRR and a designer protein - Botuyan, Maria Victoria (Nat Struct Mol Biol, 2018)
Dynamic protein interaction networks such as DNA double-strand break (DSB) signaling are modulated by post-translational modifications (PTMs). The DNA repair factor 53BP1 is a rare example of a protein whose PTM binding function can be switched on and off. 53BP1 is recruited to DSBs by recognizing histone lysine methylation in chromatin, an activity directly inhibited by 53BP1-binding protein TIRR. From X-ray structures of TIRR and a designer protein bound to 53BP1, we reveal a unique regulatory mechanism where an intricate binding area, centered on an essential TIRR arginine residue, blocks the methylated chromatin-binding surface of 53BP1 (the off switch). We find that abolishing TIRR-mediated regulation in cells via a separation-of-function 53BP1 mutation brings 53BP1 to a state of hyperactivation in response to DSBs, highlighting the key inhibitory function of TIRR. We show that this 53BP1 inhibition is relieved by TIRR-interacting RNA molecules, thus providing a proof-of-principle mechanism for RNA-triggered 53BP1 recruitment to DSBs (the on switch).